2016
DOI: 10.1111/liv.13109
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic miR‐33a/miR‐144 and their target gene ABCA1 are associated with steatohepatitis in morbidly obese subjects

Abstract: miR-33a/144 and their target gene ABCA1 may contribute to the pathogenesis of NASH in morbidly obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 38 publications
1
44
0
6
Order By: Relevance
“…However, some authors have reported that liver miR122 expression is decreased in NASH [20,26] and miR33a was increased in NASH individuals [38]. These discrepancies might be partially explained by differences in the cohort of patients studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors have reported that liver miR122 expression is decreased in NASH [20,26] and miR33a was increased in NASH individuals [38]. These discrepancies might be partially explained by differences in the cohort of patients studied.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that miR33 and miR33* represses key enzymes involved in cholesterol efflux (ABCA1 and NPC1) and fatty acid metabolism (CROT and CPT1α) in human hepatocyte cell lines [16], in agreement with our findings. Accordingly, Vega-Vadillo et al [38], in a MO cohort, have described that the relative expression of miR33a correlated inversely with ABCA1 protein levels. Moreover, miR33 target gene, CROT , correlated inversely with miR33a .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the sequencing-based analysis in the present study identified seven miRNAs that are consistently elevated across multiple IR/T2D models. Several of these seven miRNAs are in families that have been strongly connected previously to the control of insulin signaling (e.g., miR-107, miR-802, miR-34a, and miR-29a/b/c) (9, 21, 23, 26, 37, 44), obesity-related phenotypes (e.g., miR-28) (21), gluconeogenesis (e.g., miR-29a/b/c) (13,51), and/or lipid homeostasis (e.g., miR-148, miR-222 and miR-29a/b/c) (7,17,29,30,45). Liver miRNA profiles in the rodent models with metabolic dysfunction included in the present study are provided here: https://github.com/Sethupathy-Lab/metabomir.…”
Section: Seven Dysregulated Hepatic Mirnas Are Shared Across Multiplementioning
confidence: 99%
“…Zhang et al (2015) reported that upregulation of miR-125b by estrogen protected against NAFLD in female mice. Hepatic miR-33a/miR-144 and their target gene ABCA1 were associated with steatohepatitis in morbidly obese subjects (Vega-Badillo et al, 2016), and down-regulation of miR-144 elicited proinflammatory cytokine production by targeting toll-like receptor 2 in nonalcoholic steatohepatitis of high-fat-diet-induced metabolic syndrome E3 rats (Li et al, 2015). Based on our findings of increased BMI and VI with obesity resulting from DKA exposure, we posit that miR-144 and miR-125b possibly regulate lipid metabolism, and further induce lipid-metabolism-disorder syndrome.…”
Section: Introductionmentioning
confidence: 97%